The Employment Impact of Wind and Solar Energy in the US - Fang, Chao. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Economics.; Advisor: Gilbert Metcalf.; Committee: Gilbert Metcalf, and Jeffrey Zabel.; Keyword: Economics.